Robotic Technologies in Hospitality and Tourism: A PRISMA-Compliant Review on Guest Satisfaction Enhancement - Kumar, Ravi; Saifullah Khalid, Md; Agarwal , Sanskriti (PALASH A JOURNAL OF HOSPITALITY AND TOURISM SERVICE MANAGMENT, 2025)
This PRISMA-compliant systematic review examines how  robotic technologies influence guest satisfaction in the  hospitality and tourism industry. Focusing on both robotic  and AI-driven systems, the study explores their roles not only  in improving operational efficiency but also in enhancing  emotional and experiential aspects of service. A total of 26  peer-reviewed articles were selected for Thematic content  analysis was conducted using coding categories such as  anthropomorphism, usefulness, contextual fit, and human– robot collaboration. The findings show that robots enhance  efficiency, safety, and novelty, while AI technologies support  personalization and adaptive service. However, guest  satisfaction is highest in hybrid service models that integrate  robotic precision with human emotional intelligence. Guest  acceptance is shaped by several factors, including robot  design, perceived value, cultural context, and the quality of  interaction between guests and service robots.
Keywords: robotics; artificial intelligence; hybrid service models; guest satisfaction; hospitality innovation